Socio-Economic Profile of Foot-hill Villages of Punjab and its Relevance to Cost Sharing in Participatory Watershed Development - Grewal, S.S.; Dogra, A.S.; Sur, H.S; Sud, Y.P. (Journal of Soil and Water Conservation, 2022)
An Integrated Watershed Development Project supported by the World Bank is in operation since early nineties to address the problems of poverty and resource degradation in the foot-hill region of Punjab. The components of forestry, soil and water conservation, livestock improvement, rainfed agriculture and horticulture were integrated in priority watersheds using a single window system. The active involvement of communities and cost sharing by beneficiaries was made a pre-requisite. Cost sharing was, however, resisted by the rural communities on the plea of their abject poverty. A study was thus commissioned to generate information on socio-economic profile of project families and assess capacity and willingness to pay for project activities depending upon the perceived benefits. The study was conducted in 20 randomly selected villages representing the Kandi belt of Punjab. In each village 16-25 families were randomly selected giving due representation to Landless and scheduled castes. Participatory Rural Appraisal tools and a score card system was used to elicit views on perceived benefits of project components and willingness for cost sharing. Surveys revealed that only 35.3% of the total land is under cultivation and out of 64.7% unculturable land 52.2, 21.3 and 21.5% is under undivided common ownership, Panchayats and Government respectively. The SC/ST formed 35% of total population and 30% families were landless. 67.4% of land owners own less than 2 ha of rainfed land. Only 19.3% land is irrigated. 46.5% families carve out living by agriculture, 33.9% lobour and 12.6% by petty services. 46% families were yellow card holders who get subsidized ration and characterized below poverty line. 37% live in Kacha houses. The villages lack basic amenities and have poor access to markets, health services and education institutions. The survey indicated willingness to share only upto 10% of the cost on soil conservation works and that too in the form of labour, collection of sand, stones etc. depending upon flow of direct, visible, short term and substantial benefits. The cost sharing was least accepted in forestry because of long gestation. 75% cost sharing was accepted in activities like livestock health care, agro-forestry when services/goods were provided at door-step. Cost sharing upto 10% was agreed in water resource development. Common enterprises carried lowest priority for cost sharing. Study suggest that a beginning in cost sharing should be made even if it is small and the same gradually raised as dividends start flowing. Suggestions for improving cost sharing has also been made.